On the (non-)sustainability of China's development strategies - Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
This paper summarizes the main characteristics of the two major Chinese growth strategies since 1978, namely the Deng strategy (named after Deng Xiaoping) between 1978 and 2011 and the Xi strategy (named after Xi Jinping) since 2012/13. After a brief description of both strategies, I analyze in depth whether the respective reforms of the two strategies have caused sustainable or unsustainable growth and economic development. Furthermore, I derive some implications concerning the danger of a Chinese middle-income trap and propose some policy recommendations (also against the background of the Korean experience). I finally develop a growth-theoretic systematization of the arguments elaborated previously.
urn:nbn:de:hbz:708-dh4677
Keywords: F41; O10; O40; O53; 330; China; sustainability; economic development; rebalancing